(untitled) (Journal of Science and Technology, 2016)
The main objective of the paper is to test hypotheses on social class variables as determinants of the prevalence of HIV/AIDS in Sub-Saharan Africa, and to structure a schematic model for the relationship on the impact of social class on HIV/AIDS prevalence. World Bank data, 2002 World Development Indicators, are used for the analyses. Interactive graphs, with a combination of regression lines, are used as the main instruments of analysis. The indicators of social class used for the analysis are education, women’s education, Gross National Income (GNI) per capita, level of poverty, urbanisation and contraceptive usage. Inbound tourist movement is included in the analysis, though not directly linked with social class, due to it being an emerging factor in the spread of the pandemic. Education has turned out to be the main determinant of HIV/AIDS prevalence in Sub-Saharan Africa. Inbound tourism movement has emerged as an important factor in the prevalence of the disease, after education. Defects of quality of data would not be far fetched, given the lack of logistics and financial resources of most governments for the exercise, possible political manipulations and ideological biases. It is recommended that primary research at individual country levels be carried out on the effectiveness of the use of condoms, and the social class and tourist movement factors on HIV/AIDS prevalence to confirm the sub-regional findings.